The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1002/(sici)1097-4571(198605)37:3<136::aid-asi4>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between journal productivity and obsolescence

Abstract: This study examined the relationship between journal productivity and journal obsolescence for a database of references from articles dealing with desalination. Although these two variables have often been studied in isolation, no previous studies have examined their interaction within a single subject literature. It was hypothesized that those journals that were most productive would, on the average, have relatively short active lives, and that as journal productivity decreased, the average active lives of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 4 publications
3
16
0
1
Order By: Relevance
“…They observed that as thermoluminescent dosimetry literature grew it became increasingly scattered in terms of the number of contributing journals and that the rate, in terms of median citation age, of obsolescence decrease. WALLACE [1985] examined the relationship between journal productivity and journal obsolescence. After conducting a statistical test, he found that "highly productive journals did tend to have low journal median citation ages, and that high journal median citation ages were always associated with journals that were unproductive in terms of the number of references to those journals in the database."…”
Section: Literature Reviewsupporting
confidence: 66%
“…They observed that as thermoluminescent dosimetry literature grew it became increasingly scattered in terms of the number of contributing journals and that the rate, in terms of median citation age, of obsolescence decrease. WALLACE [1985] examined the relationship between journal productivity and journal obsolescence. After conducting a statistical test, he found that "highly productive journals did tend to have low journal median citation ages, and that high journal median citation ages were always associated with journals that were unproductive in terms of the number of references to those journals in the database."…”
Section: Literature Reviewsupporting
confidence: 66%
“…Bradford's Law has been extensively explored by Fairthorne (1969), Brookes (1977), Leimkuhler (1980), Wallace (1986), Nicolaisen and Hjorland (2007), and others. Drott (1981) commented specifically on the generality of the application of Bradford's Law to scientific literatures:…”
Section: Journal Selectionmentioning
confidence: 99%
“…Article life span is represented by the obsolescence indicator such as cited-half-life (Avramescu, 1979;Egghe & Rousseau, 2000a, 2000bLarivière, Archambault, & Gingras, 2008;Nicholas et al, 2005;Tona & Al, 2006;Tsay, 1998;Wallace, 1986). The normalization of citation frequency over the course of time is necessary (Kuo & Rupe, 2007;Yu, Yang, & Liang, 2010), especially for journals in modern fields of science with short article life spans, such as biology.…”
Section: Introductionmentioning
confidence: 99%